Genotoxicity in primary human peripheral lymphocytes after exposure to regular and white mineral trioxide aggregate - da Silva, Glenda N. [UNESP]; Braz, Mariana Gobbo [UNESP]; de Camargo, Elaine A. [UNESP]; Salvadori, Daisy Maria Favero [UNESP]; Ribeiro, Daniel A. [UNESP] (Elsevier, 2006)
Objective: Taking into consideration that DNA damage plays an important role in carcinogenesis, the purpose of this study was to evaluate whether regular and white mineral trioxide aggregate (MTA) are able to induce genetic damage in primary human cells. Study design: Human peripheral lymphocytes obtained from 10 healthy volunteers were exposed to 2 presentation forms of MTA at final concentrations ranging from 1 to 1000 μg/mL for 1 hour at 37°C. The negative control group was treated with vehicle control (phosphate buffer solution, PBS) for 1 hour at 37°C and the positive control group was treated with hydrogen peroxide (at 100 μM) for 5 minutes on ice. Results were analyzed by the Friedman nonparametric test. Results: The results pointed out that either regular or white MTA in all concentrations tested did not induce DNA breakage in human peripheral lymphocytes as depicted by the mean tail moment. Conclusion: In summary, our results indicate that exposure to MTA may not be a factor that increases the level of DNA lesions in human peripheral lymphocytes as detected by single cell gel (comet) assay. © 2006 Mosby, Inc. All rights reserved.
Keywords: aluminum derivative; calcium derivative; mineral trioxide aggregate; oxide; root canal filling material; silicate; adult; cell culture; cell survival; comet assay; DNA damage; drug combination; drug effect; female; human; lymphocyte; male; nonparametric test; Adult; Aluminum Compounds; Calcium Compounds; Cell Survival; Cells, Cultured; Comet Assay; DNA Damage; Drug Combinations; Female; Humans; Lymphocytes; Male; Oxides; Root Canal Filling Materials; Silicates; Statistics, Nonparametric